Influencia del taller WORK TEAM en el desarrollo de la habilidad del speaking en los estudiantes de la asignatura de inglés técnico III del séptimo ciclo de la Escuela Académico Profesional de Administración en Turismo de la Universidad Nacional de San Martín-Tarapoto 2012-II - Tejada Lopez, Kenny (2013)
The present thesis is the result of the workshop investigation WORK TEAM which allows to know the development of the skill speaking on the English language. The thesis is simple experimental type, and it was applied to students in the VII cycle of the Professional Academic School of Tourism Administration of the National University of San Martin 2012-11. The skill development "speaking" is a term which is being using to refer to such activities as speaks. The sample was shaped by students in the VII cycle of the Professional Academic School of Tourism Administration of the National University of San Martin, enrolled and assistants in the present year 2012. Then, to do the study it chose the VII cycle, 27 students in total. The recompilation of information was effected by means of pre and Post - Test. For the hypothesis contrasting was used the summation of the averages and the arithmetic mean. Done the hypothesis test and contrasted through the formulas before mentioned it has managed to conclude that the workshop WORK TEAM allows to know the development of the skill speaking on the English language, which implies that the students practices this skill during the classes, they do this in the English area.